2008
DOI: 10.1007/s11661-007-9449-2
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ and Real-Time Analysis of the Formation of Strains and Microstructure Defects during Solidification of Al-3.5 Wt Pct Ni Alloys

Abstract: Alloy solidification was investigated in situ and real time by using a unique experimental setup developed at the European Synchrotron Radiation Facility (ESRF) combining both synchrotron X-ray radiography and topography. Although synchrotron X-ray radiography enables the investigation of the solid-liquid interface of metallic alloys, white-beam synchrotron X-ray topography enables the investigation of the formation of strains and defects formation in the growing solid microstructure. In this article, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 32 publications
(32 reference statements)
1
45
0
Order By: Relevance
“…From an experimental perspective, deformation during solidification is difficult to observe and quantify [1]. From a modelling and simulation approach, the change in geometry as a result of solidification needs to be incorporated into flow and structural solvers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an experimental perspective, deformation during solidification is difficult to observe and quantify [1]. From a modelling and simulation approach, the change in geometry as a result of solidification needs to be incorporated into flow and structural solvers.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for direct observation of microstructures as solidification progresses. In particular, it has been used to examine dendrite fragmentation in aluminium alloys, a phenomena only previously accessible by post mortem characterisation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, an increasing number of real-time X-ray imaging studies of solidification microstructures and phenomena in real metals have been reported, addressing a broad variety of topics such as dendritic growth, [20][21][22][23] coarsening, [24] morphological transitions, [23] dendrite fragmentation, [25][26][27] solute diffusion and convection, [22,28] and momentum transfer relations in eutectics [29] and monotectics. [30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Most of these, and other recent in-situ studies, have been carried out with high-brilliance synchrotron radiation, where X-ray absorption-and near-field phase contrast is combined to bring about 2-D or 3D time-resolved data. [20][21][22][23][24][25][26][27]29,30] …”
Section: Introductionmentioning
confidence: 99%
“…Particular research highlights have been the study of the role of solute build-up on remelting-driven fragmentation [12], the observa-tion of misorientations emerging during solidification [13,14], imaging eutectic solidification [15,16] and identifying the importance of granular behaviour in semi-solid alloys [17].…”
mentioning
confidence: 99%